Reduced Volume and Faster Infusion Rate of Activated Prothrombin Complex Concentrate: A Phase 3b/4 Trial in Adults with Hemophilia A with Inhibitors - Zülfikar, Bülent; Mahlangu, Johnny; Nekkal, Salim Mohamed; Ross, Cecil; Uaprasert, Noppacharn; Windyga, Jerzy; Ettingshausen, Carmen Escuriola; Ploder, Bettina; Lelli, Aurelia; Gazda, Hanna T. (TH Open, 2024)
Background Activated prothrombin complex concentrate (aPCC) is indicated for bleed treatment and prevention in patients with hemophilia with inhibitors. The safety and tolerability of intravenous aPCC at a reduced volume and faster infusion rates were evaluated.Methods This multicenter, open-label trial (NCT02764489) enrolled adults with hemophilia A with inhibitors. In part 1, patients were randomized to receive three infusions of aPCC (85 ± 15 U/kg) at 2 U/kg/min (the approved standard rate at the time of the study), in a regular or 50% reduced volume, and were then crossed over to receive three infusions in the alternative volume. In part 2, patients received three sequential infusions of aPCC in a 50% reduced volume at 4 U/kg/min and then at 10 U/kg/min. Primary outcome measures included the incidence of adverse events (AEs), allergic-type hypersensitivity reactions (AHRs), infusion-site reactions (ISRs), and thromboembolic events.Results Of the 45 patients enrolled, 33 received aPCC in part 1 and 30 in part 2. In part 1, 24.2 and 23.3% of patients with regular and reduced volumes experienced AEs, respectively; 11 AEs in eight patients were treatment related. AHRs and ISRs occurred in four (12.1%) and two (6.1%) patients, respectively. In part 2, 3.3 and 14.3% of patients with infusion rates of 4 and 10 U/kg/min experienced AEs, respectively; only one AE in one patient was treatment related; no AHRs or ISRs were reported. Most AEs were mild/moderate in severity. Overall, no thromboembolic events were reported.Conclusions aPCC was well tolerated at a reduced volume and faster infusion rates, with safety profiles comparable to the approved regimen.
Keywords: aPCC; safety; treatment burden; hemophilia with inhibitors